Multi-model exploration through a large-scale visualization of the digital universe - Er, Zheng Hui (2015)
This project aims to explore various possible ways to perform navigation in the large-scale multi-model digital universe with using mobile device. The navigation application is running on iOS platform and developed using Xcode IDE from Apple Inc. The navigation application is simplified and name as navigation controller. The navigation controller should have a low learning curve and intuitive. It should be able to map to the four basic transformation operation provided by the rendering program, which are translation along z-axis to/from the attached object (zoom), rotation about z-axis to the attached object (2D rotation), rotation about an arbitrary axis with axis passing by an attached object (3D rotation) and rotation of virtual camera (panning). Four navigation prototypes have been proposed and implemented, which are multi-touch gesture controller, virtual joypad controller, orientation- sensing controller and motion-sensing controller. Multi-touch gesture controller and virtual joypad controller utilize the multi-touch features to perform navigation; while orientation-sensing controller and motion- sensing controller use a series of sensors (gyroscope, accelerometer, and magnetometer) to perform navigation. User testing has been carried out twice to examine the usability of the prototypes as well as study user behavior. Enhancements were made to improve the controllers and second test were conducted to validate them. Among the four controllers, orientation-sensing Controller is found to be the best for exploring the digital universe, users are able to complete usability testing in the shortest time and found it to be the easiest to navigate. In order to enhance user experience, directional-sensing feature is added to the mobile device by utilizing compass. This project contributes an incremental enhancement in the navigation experience of the digital universe as well as in the field of human computer interaction. From a student perspective, it provides a great exposure to product development process as well as mobile app development.